2021
DOI: 10.21608/ejbo.2021.81264.1708
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Study of Medicinal Trees and Shrubs from the Rashad District of Southern Kordofan, Sudan

Abstract: Egyptian Journal of Botany http://ejbo.journals.ekb.eg/ 25 T HIS IS the first quantitative ethnobotanical study conducted in the Rashad district, Southern Kordofan, Sudan. The objective was to collect and identify trees and shrubs used by local people for medicinal purposes and summarize local knowledge about traditional herbal medicine. Ethnobotanical data were obtained by conducting several ethnobotanical surveys, questionnaires, semi-structured interviews, field observations, inquiries, and Group gatherings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 24 publications
4
14
2
Order By: Relevance
“…This indicates that much of the ancestral knowledge that is part of the oral tradition has been transferred to the local population irrespective of socio-demographic features. Our results are contrary to findings which suggest that indigenes show more interest in traditional medicinal knowledge compared to migrants [ 12 ] and that men have better knowledge on medicinal plants than women ([ 8 , 12 , 32 ]). The similar ethnobotanical knowledge across several socio-demographic features may be because the predominant source of knowledge about medicinal plants was obtained from either parents or shared-common knowledge in the local communities.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This indicates that much of the ancestral knowledge that is part of the oral tradition has been transferred to the local population irrespective of socio-demographic features. Our results are contrary to findings which suggest that indigenes show more interest in traditional medicinal knowledge compared to migrants [ 12 ] and that men have better knowledge on medicinal plants than women ([ 8 , 12 , 32 ]). The similar ethnobotanical knowledge across several socio-demographic features may be because the predominant source of knowledge about medicinal plants was obtained from either parents or shared-common knowledge in the local communities.…”
Section: Discussioncontrasting
confidence: 99%
“…Medicinal plants are of immense significance for the healthcare needs of people worldwide. It is estimated that between 50,000 and 80,000 of the world's plant species serve as primary sources of medicine for about 80 % of the world's population ([ [8] , [9] , [10] , [11] , [12] ]). According to the World Health Organization (WHO), more than 3.5 billion people in the developing world rely on medicinal plants for their primary health ([ 13 , 14 ]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The result revealed that amongst the majority of the interviewed respondents (74 respondents), were within the age range of 36-45 years and > 56 years (Table 1). This range of age is good enough to illustrate the local traditional medicine knowledge, mainly related to the older populations who have more knowledge due to their experience accumulated with age (Bouasla & Bouasla, 2017;Miara et al, 2018;Senouci et al, 2019b;Eisawi et al, 2022). Furthermore, Sulaiman et al (2022), showed that adults in the age range of 36-45 years have very good knowledge about traditional healing of gastrointestinal diseases using plants.…”
Section: Resultsmentioning
confidence: 92%